Przedawnienie zabójstwa: brak - Krajewski, Radosław (Studia Prawnoustrojowe, 2019)
Homicide is an offence that stops being punishable if, since the moment it was committed, a period of 30 years has elapsed, which is the longest statute of limitations period under Polish criminal law. In connection with the development of forensic techniques and capabilities to detect offenders of homicide committed many years ago, the Polish legislature suggests extending the period of the statute of limitations when the deed is a crime of homicide to 40 years, which is justifed by the actual basis of re-examining old cases connected with homicide. Such a solution is a remedy between the complete non-applicability of statutory limitations and the applicability of statutory limitations in their existing form.